Prevalenza dei genotipi di HCV nella Sicilia centro-meridionale - Liborio Bellomo; Irene Maria Miraglia (Microbiologia Medica, 2003)
In this issue the prevalence of HCV genotypes was: 60.3% for 1b; 13.9% for 3a; 10.9% for 1a; 10.4% for 2a or 2c; 3.5% for 4c or 4d.The genotypes 1b, 3a, 1a and 4c or 4d are more frequent in males, while 2a or 2c have a more equalized distribution in females and males.Two female patients with an infection of 1a + 1b genotypes were observed.